TRANSMIGRATION, MULTICULTURALISM AND ITS RELATIONSHIP TO CULTURAL DIVERSITY IN EUROPE - La Torre, Christian Grililo; Montalto, Katerine Francesca (SCAD Independent, 2016)
All European societies are ethnically and culturally plural. Historically, the most significant source of cultural (not necessarily synonymous with ethnic) diversity in European nation-states has been regional, often a result of conjoining economically, socially, culturally, linguistically - and indeed ethnically - disparate places into single polities, and (certainly in Northern and Western Europe) engaging them in what the French call nationalization. This paper discusses the relationship between cultural diversity in Europe, and that international movement described as â€œtransnationalâ€ (transmigration). Though not as new or as homogeneous as some have proposed, transmigration will grow in importance in the 21st century. Groups or individuals may return to places of origin or â€œassimilateâ€ into receiving societies, but without resort to unacceptable levels of control of the movement of people, goods and ideas, transmigration will be a prominent structural feature of European societies for the foreseeable future: do we really wish to monitor every exchange between receiving and sending societies? In any case, modern systems of communication (e.g. the Internet), and the cheapness and rapidity of mass international travel make such surveillance difficult, even impossible in a transnational, globalizes world.